Assessing contributions of nucleus accumbens shell subregions to reward-seeking behavior. (1st August 2015) - Reed, Michael D.; Hildebrand, David G.C.; Santangelo, Gabrielle; Moffa, Anthony; Pira, Ashley S.; Rycyna, Lisa; Radic, Mia; Price, Katherine; Archbold, Jonathan; McConnell, Kristi; Girard, Lauren; Morin, Kristen; et al.
Highlights: We explored functional heterogeneity across nucleus accumbens shell subregions. Rats were trained to self-administer cocaine and subsequently extinguished. Amphetamine microinfusions were targeted to subregions as reinstatement tests. Targeting the dorsomedial shell led to significant reinstatement. No significant reinstatement was observed when targeting the intermediate zone. Abstract: Background: The nucleus accumbens (NAc) plays a key role in brain reward processes including drug seeking and reinstatement. Several anatomical, behavioral, and neurochemical studies discriminate between the limbic-associated shell and the motor-associated core regions. Less studied is the fact that the shell can be further subdivided into a dorsomedial shell (NAcDMS ) and an intermediate zone (NAcINT ) based on differential expression of transient c-Fos and long-acting immediate-early gene ΔFosB upon cocaine sensitization. These disparate expression patterns suggest that NAc shell subregions may play distinct roles in reward-seeking behavior. In this study, we examined potential differences in the contributions of the NAcDMS and the NAcINT to reinstatement of reward-seeking behavior after extinction. Methods: Rats were trained to intravenously self-administer cocaine, extinguished, and subjected to a reinstatement test session consisting of an intracranial microinfusion of either amphetamine or vehicle targeted to the NAcDMS or the NAcINT . Results: Small amphetamine microinfusions targeted to the NAcDMS resulted in statistically significant reinstatement of lever pressing, whereas no significant difference was observed for microinfusions targeted to the NAcINT . No significant difference was found for vehicle microinfusions in either case. Conclusion: These results suggest heterogeneity in the behavioral relevance of NAc shell subregions, a possibility that can be tested in specific neuronal populations in the future with recently developed techniques including optogenetics.